Cover Image, Volume 44, Issue 3. Issue 3 (9th March 2020) - Thum, Caroline; Ozturk, Gulustan; McNabb, Warren C.; Roy, Nicole C.; Leite Nobrega de Moura Bell, Juliana Maria
Abstract : The cover image is based on the Original Article Effects of microwave processing conditions on microbial safety and antimicrobial proteins in bovine milk by JULIANA MLNM BELL, Caroline Thum, Gulustan Ozturk et al., https://doi.org/10.1111/jfpp.14348 .